Descriptive Study of Social Relations in the Working Environment of Compagnie Ivoirienne de Coton (COIC): The Case of COIC Korhogo (Côte d’Ivoire) - Ainyakou, Taiba Germaine (European Scientific Journal, ESJ, 2025)
The objective of this study is to understand the impact of the relational environment on employees’ professional experiences, with a focus on social interactions in the workplace. It is about showing the social relations in the work environment of the Ivorian Cotton Company in the locality of Korhogo (Côte d’Ivoire). The study is part of a qualitative approach. The research instrument implemented is the interview guide, which was carried out with thirty (30) people, namely twenty-eight (28) women workers in the COIC cotton company, one (01) business manager, and one (01) team leader. This led to the results according to which the relational environment is characterized by relations with the entourage reflecting professional interactions. Indeed, social relations in the work environment play a crucial role in the productivity, well-being, and satisfaction of employees. A good social relationship can generate a climate of trust, collaboration, and mutual support between colleagues. Management policies can also contribute to strengthening social relations in the workplace.